THE EFFECT OF INTELLECTUAL INTELLIGENCE, EMOTIONAL INTELLIGENCE, SPIRITUAL INTELLIGENCE AND UNDERSTANDING OF THE ACCOUNT PROFESSIONAL CODE OF CONDUCT ON THE ETHICAL BEHAVIOR OF ACCOUNTING STUDENTS AND THEIR IMPACT ON INTEREST TO BE A PUBLIC ACCOUNTANT - Asep Kurniawan; Ai Nuraisah (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2022)
There are many differences in the results of research regarding the variables of intellectual intelligence, emotional intelligence, and spiritual intelligence on the ethical behavior of accounting students. The diversity of the results of these studies causes this research to be carried out again to obtain empirical evidence. Researchers are interested in conducting research with the title